Synthesis of aluminum nitride thin film using reactive RF-magnetron sputtering - Semblante, Oliver D.
Aluminum nitride (AIN) thin films were grown using reactive rf-magnetron sputtering with a sputtering gas composed of argon and nitrogen mixture at a partial pressure ratio of 1:3. Films were grown at 70W of rf-power without application of substrate heating from an external source. The deposited films were crack free and non-porous but were amorphous in nature as verified through SEM and XRD studies respectively.